Discrepancies between reality and expectation: can adaptive hypermedia meet the expectations of teachers? - CONLAN, OWEN (My University, 2005)
The effort to personalise eLearning has led to the development of sophisticated Adaptive Hypermedia (AH) systems that can adapt to many aspects of the learner?s characteristics or explicit preferences. However, while many of these adaptations are grounded in sound pedagogical theories, it is unclear how effective such adaptations are in supporting everyday teaching and learning processes that take place in the classroom today. This paper presents a study that explores what teachers in the UK, who have been named by their colleagues as implementing best-practice in the classroom, expect from an eLearning platform that can adapt to the individual needs of their students. The result of the study shows that there are currently some discrepancies between the teachers? expectations and what adaptive hypermedia currently offers. The paper then concludes by describing how these discrepancies can be addressed in future AH systems.
PUBLISHED
Keywords: Adaptive Hypermedia; classroom practice; eLearning personalisation